DISTRIBUTION OF GOODS AT THE BUSINESS SERVICES BUILDING FIGURE, GALING VILLAGE, GALING SUB-DISTRICT - Ahmad Mursid; Iyad Abdallah Al- Shreifeen; Rahma Helal Al_ Jbour (Review of International Economy and Finance, 2025)
This study aims to analyse the distribution system of goods in the Jasa Usaha Building Shop located in Galing Village, Galing District. The research method used is descriptive qualitative with observation techniques and in-depth interviews with shop owners, employees, and customers. The results showed that the distribution of goods in this shop uses two main channels, namely direct channels from suppliers and local distributor channels. Direct distribution from suppliers tends to be more efficient in terms of time and cost, but faces challenges in stock control and payment flexibility. Meanwhile, the route through local distributors provides advantages in terms of product diversity and stock management, albeit at a higher cost. This research suggests improving warehouse management systems and implementing information technology to facilitate monitoring and control of goods distribution. With these improvements, it is expected that the efficiency and effectiveness of the distribution of goods at the Jasa Usaha Building Store can increase, so as to provide better service to customers.